The Prion 2018 round tables (II): Aβ, tau, α-synuclein… are they prions, prion-like proteins, or what? - Eraña, Hasier (Prion, 2019)
The description of prions as causal agents of Transmissible Spongiform Encephalopathies (TSE), is nowadays accepted as an important breakthrough in biology as revealed the existence of a completely new group of pathogens and a new way of transmission for biological information. A common feature of many neurodegenerative disorders is the presence of protein aggregates in the nervous system and as evidences highlighting the similarities of these proteins with TSE-causing prions increase, the line separating the infectious prions from other protein aggregates becomes thinner than previously thought. However, instead of encompassing all these amyloidogenic proteins under the umbrella term "prion", new terminology has raised including the terms prion-like, prionoid, quasi-prion or propagon. The International Prion Conference held in Santiago de Compostela in 2018, offered the perfect forum to discuss this topic and maybe set the basis for an agreed terminology. For that, a round table was organized with several experts on the field to discuss whether AÎ², tau, Î±-synuclein and others are prions, prion-like proteins, or should be named otherwise. This commentary intends to summarize the topics discussed at the round table and shed some light on this controverted topic, drawing together the opinions of many experts participating at the session.